The Optical and Structural Properties of Undoped ZnO and Co-doped ZnO:Alx:Cdyx=1 at %, y=1, 2, 3, 5 at % Thin Films, and Their Electrical Characteristics as Photodiode - Demirbilek, Nihat; Yakuphanoğlu, Fahrettin; Kaya, Mehmet (Pleiades Publishing Ltd, 2021)
ZnO semiconductor thin films with and without Al/Cd additives were produced with sol-gel spin coating technique. Also, photodiodes with and without Al/Cd additives were prepared using the same method. The structural properties of thin films produced were examined with SEM and XRD. Optical properties were tested using UV spectrophotometer, and band gap energies of the films were analyzed using absorbance values obtained. It was observed that the films had hexagonal wurtzite crystal structure, and their band gap energies reduce with increasing amount of Cd added. The electrical characterizations of photodiodes were analyzed with phototransient current (I-t, C-t), current-voltage (I-V), capacitance-voltage (C-V) and conductance-voltage (G/w-V) measurements. The barrier height and ideality factor parameters of the diodes were calculated using thermoionic emission model. The photodiodes exhibited photosensitive behavior, and it was seen that reverse bias current raised due to raising the light intensity. The results demonstrated that the produced diodes can be used as photodiodes or photosensors in optoelectronic implementation.
Keywords: Co-doped ZnO; sol-gel; photodiode; optical properties